CORRELATION BETWEEN RELIGIOUSITY AND FREE SEX BEHAVIOR AT YOUNG ADULTHOOD - Miftah Aulia Andisti; Ritandiyono Ritandiyono (Jurnal Psikologi, 2007)
The aim of this study is to know the correlation between religiusity and free sex behavior at young adulthood. With Product Moment Pearson’s correlation shows that there is a significant correlation between religiusity and free sex behavior in young adulthood where the more religious the more impermissive the free sex behavior that can be seen.Key world: religiousity, free sex behavior, young adulthood